Pengaruh Financial Knowledge, Financial Attitude dan Locus Of Control terhadap Pengelolaan Keuangan Mahasiswa Akuntansi di Kota Batam - Wan Farida Soraya; Argo Putra Prima (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to test and evaluate financial knowledge, financial attitude and locus of control regarding the financial management of accounting students in Batam City. The population in this study was Batam University, Batam International University, Riau Islands University, Universal University and Ibnu Sina University and the sample size used purposive sampling of 100 respondents. The analytical method used in this research is a quantitative research method. The test methods used are descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests and hypothesis tests. The research results show that partially financial knowledge, financial attitude and locus of control have a positive effect on the financial management of accounting students in Batam City. Simultaneously financial knowledge, financial attitude and locus of control have a significant influence on the financial management of accounting students in Batam City.